Changes in Cortical Plasticity Across the Lifespan - Freitas, Catarina; Perez, Jennifer; Knobel, Mark; Tormos, Jose Maria; Oberman, Lindsay M.; Eldaief, Mark; Bashir, Shahid; Vernet, Marine; Peña-Gómez, Cleofé; Pascual-Leone, Alvaro (Frontiers in Aging Neuroscience, 2011)
Deterioration of motor and cognitive performance with advancing age is well documented, but its cause remains unknown. Animal studies dating back to the late 1970’s reveal that age-associated neurocognitive changes are linked to age-dependent changes in synaptic plasticity, including alterations of long-term potentiation and depression (LTP and LTD). Non-invasive brain stimulation techniques enable measurement of LTP- and LTD-like mechanisms of plasticity, in vivo, in humans, and may thus provide valuable insights. We examined the effects of a 40-second train of continuous theta-burst stimulation (cTBS) to the motor cortex (600 stimuli, 3 pulses at 50 Hz applied at a frequency of 5 Hz) on cortico-spinal excitability as measured by the motor evoked potentials (MEPs) induced by single-pulse TMS before and after cTBS in the contralateral first dorsal interosseus muscle. Thirty-six healthy individuals aged 19 to 81 years old were studied in two sites (Boston, USA and Barcelona, Spain). The findings did not differ across study sites. We found that advancing age is negatively correlated with the duration of the effect of cTBS (r = -0.367; p = 0.028) and the overall amount of corticomotor suppression induced by cTBS (r = -0.478; p = 0.003), and positively correlated with the maximal suppression of amplitude on motor evoked responses in the target muscle (r = 0.420; p = 0.011). We performed magnetic resonance imaging (MRI)-based individual morphometric analysis in a subset of subjects to demonstrate that these findings are not explained by age-related brain atrophy or differences in scalp-to-brain distance that could have affected the TBS effects. Our findings provide empirical evidence that the mechanisms of cortical plasticity area are altered with aging and their efficiency decreases across the human lifespan. This may critically contribute to motor and possibly cognitive decline.